Physiological, biochemical and molecular characterization of multiple herbicide resistance in Palmer amaranth (Amaranthus palmeri) - Nakka, Sridevi (Kansas State University, 2016)
Palmer amaranth (Amaranthus palmeri) is one of the most aggressive, troublesome and damaging broadleaf weeds in many cropping systems including corn, soybean, cotton, and grain sorghum causing huge yield losses across the USA. As a result of extensive and intensive selection of pre- and -post emergence herbicides, Palmer amaranth has evolved resistance to multiple herbicide modes of action, microtubule-, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS)-, acetolactate synthase (ALS)-, photosystem II (PS II)-, hydroxyphenylpyruvate dioxygenase (HPPD)- and more recently to protoporphyrinogen oxidase (PPO)-inhibitors. A Palmer amaranth population from Kansas was found resistant to HPPD-, PS II-, and ALS-inhibitors. The overall objective of this research was to investigate the target-site and/or non-target-site resistance mechanisms in Palmer amaranth from KS (KSR) to mesotrione (HPPD-inhibitor), atrazine (PS II-inhibitor), and chlorsulfuron (ALS-inhibitor) relative to known susceptible Palmer amaranth from Mississippi (MSS) and KS (KSS). Whole plant dose-response assays showed high level of resistance in KSR to mesotrione, atrazine and chlorsulfuron. KSR was 10-18, 178-237 and >275 fold more resistant to mesotrione, atrazine, and chlorsulfuron, respectively, compared to MSS and KSS. Metabolism studies using [¹⁴C] labeled mesotrione and atrazine demonstrated non-target-site resistance to both herbicides, particularly, enhanced metabolism of [¹⁴C] mesotrione likely mediated by cytochrome P450 monooxygenases and rapid degradation of [¹⁴C] atrazine by glutathione S-transferases (GSTs). In addition, molecular and biochemical basis of mesotrione resistance was characterized by quantitative PCR (qPCR) and immunoblotting. These results showed 4-12 fold increased levels of the HPPD transcript and positively correlated with the increased HPPD protein. Sequencing of atrazine and chlorsulfuron target genes, psbA and ALS, respectively, showed interesting results. The most common mutation (serine264glycine) associated with atrazine resistance in weeds was not found in KSR. On the other hand, a well-known mutation (proline197serine) associated with chlorsulfuron resistance was found in 30% of KSR, suggesting ~70% of plants might have a non-target-site, possibly P450 mediated metabolism based resistance. Over all, KSR evolved both non-target-site and target-site based mechanisms to mesotrione and chlorsulfuron with only non-target-site based mechanism of resistance to atrazine leaving fewer options for weed control, especially in no-till crop production systems. Such multiple herbicide resistant Palmer amaranth populations are a serious threat to sustainable weed management because metabolism-based resistance may confer resistance to other herbicides and even those that are yet to be discovered. The findings of this research are novel and valuable to recommend appropriate weed management strategies in the region and should include diversified tactics to prevent evolution and spread of multiple herbicide resistance in Palmer amaranth.
Keywords: Mesotrione; Palmer amaranth; Mechanism of herbicide resistance; Physiological and molecular basis; Atrazine; Chlorosulfuron